Mature Ovarian Teratoma: Atypical Imaging - S. Wakrim; M. EL Jdid (Case Reports in Radiology)
The incidence of a mature ovarian teratoma ranged from 20% to 30% of pediatric ovarian tumors (Sabaa et al., 2009), which is composed of well-differentiated tissues that derive from all three germ cell layers (ectoderm, mesoderm, and endoderm); it is one of the most common benign ovarian neoplasms. In this case report, we discuss a 9-year-old female patient who presented with abdominal pain and distended abdomen, for which she had an abdominal ultrasound and magnetic resonance imaging. The histopathological exam, after a laparotomy, showed a mature ovarian teratoma.